2014
DOI: 10.1186/1756-8722-7-31
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of single dose of recombinant human IL-12 versus placebo for restoration of hematopoiesis and improved survival in rhesus monkeys exposed to lethal radiation

Abstract: BackgroundThe hematopoietic syndrome of the acute radiation syndrome (HSARS) is a life-threatening condition in humans exposed to total body irradiation (TBI); no drugs are approved for treating this condition. Recombinant human interleukin-12 (rHuIL-12) is being developed for HSARS mitigation under the FDA Animal Rule, where efficacy is proven in an appropriate animal model and safety is demonstrated in humans.MethodsIn this blinded study, rhesus monkeys (9 animals/sex/dose group) were randomized to receive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 24 publications
1
33
1
2
Order By: Relevance
“…The consistent survival benefit we have demonstrated in three randomized vehicle-controlled studies of rHuIL-12 in NHP without the use of fluids, antibiotics, or blood products supports the potential for this agent as a viable radiation medical countermeasure in the mass casualty scenario. It should be noted that the finding of numerical, but not statistical, significance for rHuIL-12 when compared to control in the prespecified log rank and two-tailed chi-square analyses in this study appears to be owing to the higher than expected survival rate in the control group (36%) at 700 cGy, compared to 11% of survival for controls in our previous NHP study that used the same radiation dose as was used in this study and which showed statistically significant survival benefit of rHuIL-12 relative to control at doses of 50, 100, 250, and 500 ng/kg [7]. Nevertheless, the totality of the data in this study demonstrates a numerical survival benefit of rHuIL-12 over both the vehicle control and a statistically significant benefit over the G-CSF control, the latter being numerically worse and statistically not different from the vehicle control.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The consistent survival benefit we have demonstrated in three randomized vehicle-controlled studies of rHuIL-12 in NHP without the use of fluids, antibiotics, or blood products supports the potential for this agent as a viable radiation medical countermeasure in the mass casualty scenario. It should be noted that the finding of numerical, but not statistical, significance for rHuIL-12 when compared to control in the prespecified log rank and two-tailed chi-square analyses in this study appears to be owing to the higher than expected survival rate in the control group (36%) at 700 cGy, compared to 11% of survival for controls in our previous NHP study that used the same radiation dose as was used in this study and which showed statistically significant survival benefit of rHuIL-12 relative to control at doses of 50, 100, 250, and 500 ng/kg [7]. Nevertheless, the totality of the data in this study demonstrates a numerical survival benefit of rHuIL-12 over both the vehicle control and a statistically significant benefit over the G-CSF control, the latter being numerically worse and statistically not different from the vehicle control.…”
Section: Discussionmentioning
confidence: 52%
“…In conclusion, the results from this randomized vehicle-controlled blinded Phase 2-equivalent study in NHP build upon the results from our proof-of-concept study [6] and a dose-escalation study of rHuIL-12 in lethally irradiated rhesus monkeys [7] by demonstrating, in a large cohort of male and female monkeys, that a single dose of rHuIL-12 alone, without antibiotics, fluids, blood products, or other growth factors, increases survival compared with a regimen of 18 consecutive days of treatment with G-CSF, the currently recommended treatment for radiation victims. These findings support the further development of rHuIL-12 under the FDA Animal Rule as a single agent to counteract the effects of HSARS in humans.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…We initially focused our examination on the expression of IL-12 and transforming growth factor ␤ (TGF-␤) transcripts. IL-12, a T cell-stimulating factor involved in the differentiation of naive T cells into Th1 cells, has been shown to promote hematopoiesis and stem cell engraftment after ionizing radiation (69,70). TGF-␤ is also involved in stem cell differentiation and T cell regulation/differentiation and suppresses general hema-FIG 5 HCMV-induced EGFR signaling enhances IE1 expression in primary monocytes.…”
Section: Resultsmentioning
confidence: 99%